Chartering contracts and financial performance of U.S. listed shipping firms - Kouspos, Andreas; Panayides, Photis; Tsouknidis, Dimitris (My University, 2025)
This paper investigates the relationship between chartering contracts and the financial performance of U.S.-listed shipping firms. We use public data from SEC’s 20-F forms for U.S. listed shipping firms to construct a unique dataset of vessel chartering decisions, comprising 8,733 vessel-year observations. We rely on panel data regressions to show that managing the notoriously high freight rate risk, by employing the greatest part of a shipping firm’s fleet under time-charter contracts rather than voyage (spot) charter contracts, creates corporate value as it increases financial performance. This main result has several important implications regarding mainstream business decisions of shipping firms, such as vessels’ operations and chartering.
Keywords: panel data; listed shipping firms; Chartering contracts; firm performance;; U.S.